Self-Remanufacturing or Outsourcing? Hybrid Manufacturing System With Remanufacturing Options Under Yield Uncertainty - Miaomiao Wang; Tao Tian; Xiaoxi Zhu (IEEE Access, 2019)
Yield uncertainty widely exists in manufacturing industries. Because of the particularities of the recovery and production processes, remanufacturing is seriously affected by the uncertainty of the production process, which also affects the remanufacturing choice of enterprises. In this paper, we focus on the case where a make-to-order type manufacturer is confronted with the strategic option of obtaining core materials by self-remanufacturing or outsourcing new cores. Through a stochastic modelling approach, a two-echelon closed-loop supply chain is constructed to capture the manufacturer's sourcing strategy and production planning by considering yield uncertainty in both the remanufacturing and production stages. We first examine the case of a deterministic recovery rate. The results show that regardless of whether the firm chooses to remanufacture or buy new core materials, the expected profit of the (re)manufacturer is always concave. Then, in the case of a random recovery rate, we show that the distribution bounds are important and play key roles in deciding the strategic option of self-remanufacturing or outsourcing. By comparing the upper and lower bounds of the recovery rate with the procurement cost of new raw material and used product, three production/sourcing strategies, namely, using remanufactured cores only, outsourcing new material only and jointly using the two materials, are investigated. The optimal procurement quantity and the optimal production input are derived to maximize the (re)manufacturer's expected profits under the three scenarios. Finally, we perform sensitivity analysis of the impact of yield uncertainty on the optimal results. The results show that when the shortage cost increases, the collection quantity increases faster than the production input, which implies that a “bullwhip effect” exists in the proposed two-period collection and production system. The conclusions of this paper can be applied to remanufacturing in related enterprises to provide production and procurement decision support for managers and to promote the efficiency of closed-loop supply chains.